2015
DOI: 10.1007/s10943-015-0125-3
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Descriptive Study of Occupational Therapy Students’ Perceptions and Attitudes Towards Spirituality and Spiritual Care in Occupational Therapy Education

Abstract: Mthembu, T.G. et al. (2016). A cross-sectional descriptive study of occupational therapy students' perceptions and attitudes towards spirituality and spiritual care in occupational therapy education. Journal of religion and Health, 55: 1529Health, 55: -1545 Abstract Spirituality and spiritual care both have received increased attention over the course of this past decade from different disciplines. However, for many years, in the occupational therapy profession, the importance of spirituality and spiritual c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
13
0
1
Order By: Relevance
“…Factor 4 (Clients' spiritual needs) had two variables related to spirituality which involve clients' and clinician responsibilities. These findings support the assertion of Hammel 30, and Mthembu, Roman and Wegner 32 that client-centred practice should enhance collaborative partnerships between occupational therapists and clients to promote autonomy, choice and control, as well as respect for clients' abilities.…”
Section: Clients' Spiritual Needssupporting
confidence: 80%
“…Factor 4 (Clients' spiritual needs) had two variables related to spirituality which involve clients' and clinician responsibilities. These findings support the assertion of Hammel 30, and Mthembu, Roman and Wegner 32 that client-centred practice should enhance collaborative partnerships between occupational therapists and clients to promote autonomy, choice and control, as well as respect for clients' abilities.…”
Section: Clients' Spiritual Needssupporting
confidence: 80%
“…The answers by the nursing care employees included in the study regarding the first part of SSCRS have shown an understanding of spiritual care in nursing especially as being kind, caring, spending more time with an individual patient, being supportive and respecting the patient's privacy, their dignity, and religious and cultural beliefs. Other research conducted by means of the SSCRS questionnaire in various cultural and religious environments has also shown that the nursing staff generally consider that the attitude towards patients (care, optimism, support) and therapeutic communication were the key elements of spiritual care in nursing (Kostak & Celikkalp, 2016;Kaddourah, et al, 2018) and in other health care fields such as occupational therapy (Mthembu, et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…Odgovori anketiranih zaposlenih v zdravstveni negi na prvi sklop SSCRS kažejo razumevanje duhovne oskrbe v zdravstveni negi predvsem kot izražanje prijaznosti, skrbi, posvečanje časa pacientu, podpore ter spoštovanja zasebnosti pacientov, njihovega dostojanstva ter verskih in kulturnih prepričanj. Tudi druge raziskave, opravljene v različnih kulturnih in verskih okoljih z vprašalnikom SSCRS, kažejo prevladujoče prepričanje zaposlenih v zdravstveni negi, da sta odnos do pacienta (skrb, izražanje pozitivnih čustev, podpora) in terapevtska komunikacija ključna elementa duhovne oskrbe v zdravstveni negi (Kostak & Celikkalp, 2016;Kaddourah, et al, 2018), pa tudi v drugih zdravstvenih strokah, na primer v delovni terapiji (Mthembu, et al, 2016).…”
Section: Diskusijaunclassified
“…This 5-point Likerttype scale was designed to measure nurses' perceptions of spirituality and spiritual care within nursing. Cronbach's alpha coefficients ranging from .64 to .76 have been reported for total scores (e.g., McSherry et al, 2002;Mthembu, Roman, & Wegner, 2016). Four identified subscales included spirituality, spiritual care, religiosity, and personalized care.…”
Section: Demographic Collection Toolmentioning
confidence: 99%